dass ((…)) ich des nich WEISS- (.) weißte, Gesprächsorganisierende Funktionen der weißt du-Konstruktion im gesprochenen Deutsch Zusammenfassung - Piosik, Michał (Die deutsche Sprache in vielfältigen Forschungsparadigmen. Beiträge polnischer Doktoranden anlässlich der 9. Linguistischen Tagung–Łódź, 09.05.2015, 2016)
The main aim of the present article is to analyse the weißt du-construction in German daily conversation. In sections 1. and 2., I discuss the study’s goals, the used corpus and methodology. Thereafter, I highlight the codified semantic meaning of wissen (3.1.) and present the relevant results of the actual quantitative and qualitative analysis of the research material consisting of 116 FOLK-transcripts (=40 hours 33 minutes; section 3.2.). In section 3.3., I discuss the most important formal and functional features of three types of the weißt du-construction distinguished due to the analysis (the initial, the parenthetic and, last, but not least, the final ones). The results are illustrated with exemples from the FOLK-corpus. The last part of the study, i.e. section 4, offers a succinct summary of the subject of my research and of the results. Based on the approach presetnted in Imo (2007), it also shows a construction grammatical frame for weißt du as a discourse marker.